2022
DOI: 10.3390/ma15175871
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Hydrogels: New Materials for Biosensing and Biomedical Applications

Abstract: Peptide-based hydrogels have attracted increasing attention for biological applications and diagnostic research due to their impressive features including biocompatibility and biodegradability, injectability, mechanical stability, high water absorption capacity, and tissue-like elasticity. The aim of this review will be to present an updated report on the advancement of peptide-based hydrogels research activity in recent years in the field of anticancer drug delivery, antimicrobial and wound healing materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 167 publications
0
51
0
Order By: Relevance
“…The insurgence of resistance to multiple antimicrobial agents in pathogenic bacteria is already a major medical concern, compromising the clinical outcomes of many currently used drugs. By 2050, it is predicted that multidrug-resistant (MDR) pathogens will be causing more than 10 million deaths every year [ 1 , 2 , 3 , 4 , 5 , 6 ]. Unfortunately, the insurgence of MDR phenomena has overcome the rate of development of new antibiotics; therefore, exploring efficient or even alternative therapies seems urgent and necessary [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insurgence of resistance to multiple antimicrobial agents in pathogenic bacteria is already a major medical concern, compromising the clinical outcomes of many currently used drugs. By 2050, it is predicted that multidrug-resistant (MDR) pathogens will be causing more than 10 million deaths every year [ 1 , 2 , 3 , 4 , 5 , 6 ]. Unfortunately, the insurgence of MDR phenomena has overcome the rate of development of new antibiotics; therefore, exploring efficient or even alternative therapies seems urgent and necessary [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dipeptides are minimalistic peptides that can also form hydrogels through molecular self-assembly . Dipeptide-based hydrogels have been investigated as important tools in drug delivery, tissue regeneration, 3D cell culture, and imaging. Dipeptide hydrogelators result from the molecular preorganizations and noncovalent interactions between peptide strands . Therefore, this new class of peptides is promiscuous for imparting shear thinning and self-healing properties in response to external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide-derived self-assembled hydrogels have been particularly effective for drug delivery applications, including the delivery of protein payloads. Koutsopoulos et al demonstrated that supramolecular hydrogels formulated from the self-assembled Ac-(RADA) 4 -NH 2 peptide facilitated the controlled release of lysozyme, trypsin inhibitor (TI), BSA, and immunoglobulin G (IgG) . They found that the rate of protein release from these neutral hydrogels decreased with increasing molecular weight of the payload, and that released proteins maintained functional catalytic/binding activity.…”
Section: Introductionmentioning
confidence: 99%